Synthesis and photophysical properties of antimony and lead phthalocyanines,CHAPTER ONE: - Modibane, Kwena Desmond,Guest (Rhodes University, Faculty of Science, Department of Chemistry, 2009)
This work hereby presents the synthesis, spectroscopic and photophysical properties of newly synthesized lead (PbPc) and antimony (SbPc) phthalocyanines. The complexes are either unsubstituted or substituted at the peripheral and non-peripheral positions with phenoxy, 4-t-butylphenoxy and 4-benzyloxyphenoxy groups. The photophysical properties of these complexes were studied in dimethylsulfoxide, dimethylformamide, toluene, tetrahydrofuran and chloroform as solvents. The fluorescence spectra for PbPc complexes were different to that of the excitation spectra due to demetallation upon excitation. On the other hand, the excitation spectra of oxidized antimony (Sb(V)Pc) derivatives were found to be similar to absorption spectra. High triplet quantum yields for PbPc and SbPc complexes ranging from 0.70 to 0.86, low triplet lifetimes (20"“60 Î¼s in DMSO, while they were <10 Î¼s in the rest of the solvents) and low fluorescence quantum yields were observed and is attributed to the presence of heavy atoms (Pb and Sb ions). The nonlinear optical properties of PbPc complexes were studied in dimethylsulfoxide. The optical limiting threshold intensity (Ilim) for the PbPc derivatives were calculated and ranged from 2.1 to 6.8 W/cm2. The photodegradation studies of the PbPc and SbPc complexes synthesized showed that then are stable.
Keywords: Phthalocyanines; Photochemistry; Antimony compounds; Lead compounds